Do Swedish Schools Discriminate against Children with Disabilities? - Ali M. Ahmed; Mats Hammarstedt; Karl Karlsson (Research Institute of Industrial Economics (IFN), 2020)
We present results from a field experiment in which fictitious parents to children with certain types of disabilities, attention deficit hyperactivity disorder (ADHD) and type 1 diabetes mellitus (T1DM), make inquires to Swedish schools about admission for their children to the compulsory preschool class. Our results reveal that Swedish schools discriminated against children with these disabilities and that discrimination is most prevalent in private schools. Private schools discriminated against boys with ADHD and T1DM and against girls with ADHD. Furthermore, public schools discriminated against girls with ADHD. One potential effect of our results is that children with disabilities are referred to less attractive schools than children with no such medical conditions. These results may have implications for the possibilities for individuals with ADHD and T1DM to succeed in the labor market in the long run.
Keywords: I24; J14; J71; 330; Preschools; Disabilities; Discrimination